Perkembangan Gagasan I’jaz Al-Qur’an Menurut Isa J. Boullata - Ulummudin, Ulummudin (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2020)
This article examines about the history of i’jaz development of the Qur’an which is written by Issa J. Boullata. According to him, this idea emerged in the early third century of Hijriyah. In its progress, classicalIslamic scholar who is the most influential figure in this field is Abdul Qahir al-Jurjani and al-Zamakhsyari. Meanwhile, in the contemporary era, Sayyid Quthub and Aisyah bint Syati take significant place. Boullata is able to present the history of i’jaz comprehensively. However, there is contradiction in his explanation. He states that when al-Qur’an was revealed, Arab society were not balaghah expert and lirerary critic. In fact, they had capability on it.In addition, there was a missing link between al-Zamakhsyari (d.538 H) and Muhammad Abduh (1905). In that long period, scholars of i’jaz were not described.